2013
DOI: 10.1620/tjem.230.255
|View full text |Cite
|
Sign up to set email alerts
|

Non-Work-Related Personal Events Contribute to Depressive Symptoms in Japanese Discretionary Workers

Abstract: In Japan, the number of workers with depressive symptoms has increased recently, and long working hours are considered one of the main contributing factors. Currently, the number of workers engaging in discretionary work is small but is expected to increase, as a diverse method of employment is believed to contribute to workers' well-being. However, the factors related to discretionary workers' depressive symptoms are unclear. This study aimed to identify the factors associated with depressive symptoms in disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Financial difficulties were frequently listed as problems of most concern in the current study, followed by working conditions. This result is somewhat expected as financial difficulties have often been suggested as a risk factor in psychological distress during other studies [ 5 , 7 , 29 ]. In the current investigation, the presence of financial difficulties was based on each participant’s self-perception, rather than a quantitative assessment of income or indebtedness.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Financial difficulties were frequently listed as problems of most concern in the current study, followed by working conditions. This result is somewhat expected as financial difficulties have often been suggested as a risk factor in psychological distress during other studies [ 5 , 7 , 29 ]. In the current investigation, the presence of financial difficulties was based on each participant’s self-perception, rather than a quantitative assessment of income or indebtedness.…”
Section: Discussionsupporting
confidence: 71%
“…Divorce, a generally negative outcome of marriage, is a major factor that affects the mental health of Japanese men, even increasing their risk of suicide [ 5 , 6 ]. Statistics on the reasons for divorce in Japan indicate that the most common reason is mismatch of characteristics (64% for male and 44% for female), followed by domestic violence, and psychological conflicts between wives and husbands [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…dismissal from work, illness or a serious accident), to level of time investment in work over the years. Previous research has shown that life events exert an effect on subjective well-being (Luhmann et al, 2012), stress (Bono et al, 2013;Sarason et al, 1978) and affective states (Mignonac and Herrbach, 2004;Ogami et al, 2013). Note, however, that like change in financial needs, certain work/nonwork events are deemed to bring about a change in a specific direction (positive or negative) in time investment in work.…”
Section: Introductionmentioning
confidence: 99%